2014
DOI: 10.1212/wnl.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II randomized trial of aerobic exercise in Parkinson disease in a community setting

Abstract: Objectives: To (1) investigate effects of aerobic walking on motor function, cognition, and quality of life in Parkinson disease (PD), and (2) compare safety, tolerability, and fitness benefits of different forms of exercise intervention: continuous/moderate intensity vs interval/alternating between low and vigorous intensity, and individual/neighborhood vs group/facility setting. Methods:Initial design was a 6-month, 2 3 2 randomized trial of different exercise regimens in independently ambulatory patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 41 publications
5
151
1
Order By: Relevance
“…Several studies have demonstrated that regular aerobic exercise improves balance and motor symptoms, reduces indicators of depression, improves cardiovascular health, and enhances overall quality of life in PD patients in short-term and long-term follow up studies alike (Canning et al, 2015;Frazzitta et al, 2015;Frazzitta et al, 2014;Uc et al, 2014). Two studies showed that these improvements in PD symptoms correlated with a normalization in the level of circulating biomarkers of PD.…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 99%
“…Several studies have demonstrated that regular aerobic exercise improves balance and motor symptoms, reduces indicators of depression, improves cardiovascular health, and enhances overall quality of life in PD patients in short-term and long-term follow up studies alike (Canning et al, 2015;Frazzitta et al, 2015;Frazzitta et al, 2014;Uc et al, 2014). Two studies showed that these improvements in PD symptoms correlated with a normalization in the level of circulating biomarkers of PD.…”
Section: Anti-inflammatory Effects Of Physical Activity and Exercise mentioning
confidence: 99%
“…Recent evidence suggests that exercise has multiple important health benefits that should be leveraged by patients with PD. Exercise improves the physical and mental functioning levels and quality of life for patients with PD, [22][23][24][25][26] and early intervention with exercise can prevent falls. 26 It should be recommended to all patients with PD.…”
Section: Measure 10mentioning
confidence: 99%
“…Exercise improves the physical and mental functioning levels and quality of life for patients with PD, [22][23][24][25][26] and early intervention with exercise can prevent falls. 26 It should be recommended to all patients with PD. The work group declined to develop an exception for this measure as it is believed that all patients can benefit from this counseling and counseling must be tailored to individual patient needs.…”
Section: Measure 10mentioning
confidence: 99%
“…These integrative therapies or exercises are helpful in improving rigidity, balance disorder, and parts of the non-motor symptoms, and some patients have self-initiated these activities or treatments during all periods or stages of anti-parkinsonism treatment [31,32,33]. Psychological guidance is useful to reduce depression, and health care is important to prevent inflammation, nutrition impairment, falls, and fractures.…”
Section: Other Integrative Treatment or Exercisesmentioning
confidence: 99%